2014
DOI: 10.1073/pnas.1318810111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation associated with euphorigenic effects of d -amphetamine is associated with diminished risk for schizophrenia and attention deficit hyperactivity disorder

Abstract: Here, we extended our findings from a genome-wide association study of the euphoric response to d-amphetamine in healthy human volunteers by identifying enrichment between SNPs associated with response to d-amphetamine and SNPs associated with psychiatric disorders. We found that SNPs nominally associated (P ≤ 0.05 and P ≤ 0.01) with schizophrenia and attention deficit hyperactivity disorder were also nominally associated with d-amphetamine response. Furthermore, we found that the source of this enrichment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Similarly, prior reports of familial co-transmission of ADHD and depression [54] have been extended by showing shared SNP heritability between the two disorders [98]. Using a novel drug challenge paradigm, Hart et al [111] found that the polygenic scores for both schizophrenia and ADHD were associated with the euphoric response to amphetamine, which suggests that the genetic association between these disorders may be due to variants in the neural systems regulating the euphoric response to amphetamine.…”
Section: Common Variant Adhd As a Polygenic Disordermentioning
confidence: 87%
“…Similarly, prior reports of familial co-transmission of ADHD and depression [54] have been extended by showing shared SNP heritability between the two disorders [98]. Using a novel drug challenge paradigm, Hart et al [111] found that the polygenic scores for both schizophrenia and ADHD were associated with the euphoric response to amphetamine, which suggests that the genetic association between these disorders may be due to variants in the neural systems regulating the euphoric response to amphetamine.…”
Section: Common Variant Adhd As a Polygenic Disordermentioning
confidence: 87%
“…SNPs in VAC14 associated with docetaxel-induced peripheral neuropathy (46), and the gene was recently shown to be mutated in pediatric-onset neurological disease (47). Beyond chemotherapy studies, genetic variants that associate with the euphoric effects of d -amphetamine significantly overlap with variants that decrease risk for schizophrenia and attention deficit hyperactivity disorder (48). The broad implication is that adverse drug events and related, non-drug-induced phenotypes may have related genetic etiologies, especially in the absence of large effects from genetic variation in enzymes involved in drug absorption, metabolism, distribution or excretion.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that humans have varying degrees of sensitivity to social isolation; however, the question of whether or not the genetic basis of this variability also underlies the risk for common psychiatric diseases remains largely unexplored. We have previously reported that genetic variation in the initial sensitivity to the euphoric effects of amphetamine is genetically correlated with the risk for both schizophrenia and ADHD (Hart et al, 2014). That provocative finding Table 4 Associations between Polygenic Scores for Neuroticism from SSGAC (Okbay et al, 2016) The testing set was an independent set using the data of HRS; the polygenic scores have been standardized, and hence the β coefficients from the Neuroticism linear regression model correspond to a 1 SD change in the polygenic score.…”
Section: Discussionmentioning
confidence: 99%